PARLIAMENTARY OPPOSITION IN CENTRAL ASIA: PROGRESS, PROBLEMS AND PROSPECTS - ERGASHEV, Bakhodyr (CENTRAL ASIA AND THE CAUCASUS, 2008)
Anyone wishing to study political modernization should not ignore the recent problems born by the party-building process. The institution of parliamentary opposition and its evolution are probably the most complicated of them for the simple reason that legislatures are a relatively new and fairly progressive phenomenon in the region able to stimulate democratic processes on their own. In addition, the parliamentary parties have enough political weight to promote the best possible laws. According to the generally accepted definition, the parliamentary opposition is a group of parliamentarians or the parliamentary faction of a party does not present in the Cabinet and opposing it on issues of fundamental importance.1 Social and political thought in Central Asia is paying enough attention to the opposition as the region’s political reality.2 So far, however, the parliamentary opposition as the most complicated part of political opposition has escaped attention. This article attempts to assess the experience of other countries and analyzes domestic phenomena and the meaning of the changes to reveal their hidden mechanisms and impact on the local po litical regimes and take a look at the future of parliamentary opposition. I proceed from the fact that this institution has been developing in countries “that have never known a multi-party system, professional parliaments, legal opposition, independent press, real freedom of conscience, or independent trade unions, and where non-governmental organizations have been terra incognita.”3